Antimicrobial resistance and stewardship. Issue 1 (5th January 2015) - Birnbaum, David
Abstract : Purpose: – The purpose of this paper is to report on recent developments concerning promotion of initiatives to contain the spread of resistance to antimicrobial drugs. Design/methodology/approach: – Narrative review. Findings: – In 2014, an American executive order made combating antimicrobial resistance a national priority. While this and other developments convey a message of growing urgency, the core elements required and challenges ahead are neither new nor unexplored. The quantity and quality of antimicrobial stewardship research over the past decade has added little to what already was known. Suppressing evolution of emerging drug resistance and containing emergence of resistant strains as on-going activities to maintain a balance might be a more realistic statement of the problem than framing it as winning a war. It remains to be seen how well those in the front lines of healthcare epidemiology and infection control shape framing of this problem before American federal and state agencies respond to their presidential directive by relaying marching orders through laws, rules, regulations, financial incentives and penalties. It remains to be seen whether the next decade will be more successful than the last given a more recent emphasis on the strategy of bundling small sets of practical key measures into effect, and the involvement of public health departments in support of antimicrobial stewardship. Unlike a generation ago, it also is clear that international trade and travel make this a global problem. America cannot be expected to resolve emerging drug resistance alone even if containment efforts within its own borders are successful, but like other developed countries it can be expected to have vested self-interests in promoting global solutions to this complex problem. Originality/value: – This report brings together recent American government policy decisions and insights from two noteworthy interdisciplinary conferences.